GERAKAN PEMIKIRAN KEAGAMAAN RAUSAYANFIKR DI YOGYAKARTA - Ajuba, Taufik (Farabi, 2023)
This review aims to examine how the intellectual movement of the Rausyan Fikr Foundation can play a significant role in shaping the discourse of Islamic philosophical scholarship and the extent to which the influence and reality of the Rausyan Fikr Foundation's religious intellectual movement in Yogyakarta. This paper employs a qualitative method and analyzes the extent to which the preaching methods developed by the Rausyan Fikr Foundation are linked to the Islamic Republic of Iran. The sociology of religion is the author's choice for analyzing the role of the Rausyan Fikr Foundation's religious intellectual movement. The findings of this paper indicate that the intellectual movement of the Rausyan Fikr Foundation has Islamic philosophy discourse as its identity. The works of Shia scholars in Iran serve as the main reference for activists of the Rausyan Fikr Foundation. With idealism as their foundation, the Rausyan Fikr Foundation is not trapped by practical political interests because the Foundation itself has independent business units through the sale of Shia-oriented books. It is this idealism that consistently garners positive responses for the Rausyan Fikr Foundation, especially among students.